Unravelling the association between renal functions and anti thyroid peroxidase antibody levels in newly diagnosed cases of hypothyroidism in elderly - Devi D, Gayathri; Behera, Kishore Kumar; Mangaraj, Manaswini; Saharia, Gautom Kumar (Frontiers in Endocrinology, 2025)
IntroductionElderly population is more susceptible to both hypothyroidism and chronic kidney disease (CKD) independently and it is very crucial to assess kidney function in elderly hypothyroid patients in relation to autoimmunity. There are previous studies showing a correlation between eGFR and TSH, T3, and T4 in the elderly population but no such studies correlating the estimated GFR (eGFR) with the anti-thyroid antibodies of elderly hypothyroid patients are available. This study aimed to assess renal function in newly diagnosed elderly hypothyroid patients and correlate findings with anti-thyroid peroxidase (anti-TPO) levels.MethodsWe conducted a cross-sectional study with 128 participants aged 60 years and above after obtaining ethics committee approval. All cases were newly diagnosed patients of hypothyroidism whether clinical or subclinical. The control group consisted of age and sex matched individuals with normal thyroid profile status. Fasting blood samples were collected and serum thyroid parameters, glycemic and renal markers were evaluated, and statistical analyses were performed.ResultsHypothyroid patients exhibited elevated anti-TPO levels and markers of renal dysfunction, including increased urea, uric acid, and urine albumin/creatinine ratio. Multiple regression analysis identified anti-TPO as an independent predictor of kidney function. Subgroup analysis revealed significantly lower eGFR and elevated renal markers in anti-TPO positive patients.DiscussionThe interplay between thyroid dysfunction and renal impairment is particularly significant in the elderly, who are more vulnerable to both conditions. Elevated anti-TPO levels are associated with renal dysfunction in elderly hypothyroid patients, suggesting a potential role for anti-TPO in renal impairment.